Essential Role of the ε Subunit for Reversible Chemo-Mechanical Coupling in F(1)-ATPase - Watanabe, Rikiya (Biophys J, 2018)
F(1)-ATPase is a rotary motor protein driven by ATP hydrolysis. Among molecular motors, F(1) exhibits unique high reversibility in chemo-mechanical coupling, synthesizing ATP from ADP and inorganic phosphate upon forcible rotor reversal. The ε subunit enhances ATP synthesis coupling efficiency to > 70% upon rotation reversal. However, the detailed mechanism has remained elusive. In this study, we performed stall-and-release experiments to elucidate how the ε subunit modulates ATP association/dissociation and hydrolysis/synthesis process kinetics and thermodynamics, key reaction steps for efficient ATP synthesis. The ε subunit significantly accelerated the rates of ATP dissociation and synthesis by two- to fivefold, whereas those of ATP binding and hydrolysis were not enhanced. Numerical analysis based on the determined kinetic parameters quantitatively reproduced previous findings of two- to fivefold coupling efficiency improvement by the ε subunit at the condition exhibiting the maximum ATP synthesis activity, a physiological role of F(1)-ATPase. Furthermore, fundamentally similar results were obtained upon ε subunit C-terminal domain truncation, suggesting that the N-terminal domain is responsible for the rate enhancement.